Rational Economic Man og Bounded Rationality - Nogle betragtninger over rationalitetsbegrebet i økonomisk teori - Finn Olesen (University of Southern Denmark, Department of Environmental and Business Economics (IME), 2006)
– As a core element in economic theory we accept that economic agents behave rationally. They either maximize their profit or their utility. But is the behavior of the rational economic man really a realistic assumption? Or is Simon right when he argues that firms satisfy rather than maximize? In this paper we dis-cuss some aspects of bounded rationality and pose the question: Is this the way out? Uden på nogen måde at ville kompromittere mine kolleger, Tommy S. Poulsen og Eva Roth, skal jeg takke dem begge for kommentarer til en tidligere version at dette papir.
Keywords: 330